Large displacement optical switching mechanism using SMA microactuator and magnetic latch - Bhuiyan, Md. Moinul Islam; Haga, Yoichi; Esashi, Masayoshi (2004)
POF (Plastic Optical Fiber) is more suitable than the quartz optical fiber for indoor LAN (Local Area Network), for example in-home or office networks because of its flexibility and ease of connection by relatively large core diameter.1 x 2 optical switches for indoor LAN using POF have been developed. For switching by movement of a POF, large displacement is necessary as core diameter is large (e.g.0.486mm). A SMA (shape memory alloy) coil actuator is used for large displacement and a magnetic latching system is used for fixing the position of the shifted POF. Switching speed is less than 0.5 second and the insertion loss of the fabricated switch is 0.40 to 0.50dB. The insertion loss is 0.06 to 0.09dB using index-matching oil. PCF (Plastic Clad Fiber)has also large core diameter (e.g. 0.20mm) and an optical switches using PCF will be useful for short distance network between buildings.